Associations between physical activity levels and quality of life dimensions among Saudi female university students: a cross-sectional analysis using WHOQOL-BREF and IPAQ-SF - Faisal A. Barwais (Physical Education of Students, 2025)
Background and Study Aim. Physical activity is a key determinant of health and well-being, particularly among young adults. University students often face lifestyle changes that can affect their overall quality of life (QoL). The present study aimed to explore the relationship between physical activity levels and QoL among Saudi female university students.